Explor Drug Sci 2023
DOI: 10.37349/eds.2023.00024
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals for mitigating the COVID-19 crisis: evidence from pre-clinical and clinical studies

Atri Das,
Swarnali Khan,
Syamal Roy
et al.

Abstract: The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in December 2019 quickly escalated to pandemic levels and had a severe impact on public health. There are 761 million confirmed coronavirus disease 2019 (COVID-19) cases, with over 6.88 million deaths worldwide till March 2023. Severe cases of the disease caused critical respiratory failure followed by multiorgan involvement. Clinical escalation of COVID-19 has been correlated with markedly increased plasma inflammatory mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 235 publications
0
2
0
Order By: Relevance
“…Among these, the most studied are resveratrol, quercetin, hesperidin, curcumin, myricetin, and betulinic acid, which were proposed as SARS-CoV-2 inhibitors [159]. Regarding natural products, resveratrol, curcumin, and quercetin have demonstrated in vitro antiviral activity against SARS-CoV-2, and in vivo, a nebulised formulation has been demonstrated to alleviate the respiratory symptoms of COVID-19 [158,159,161].…”
Section: Drug Repurposing For Covid-19mentioning
confidence: 99%
“…Among these, the most studied are resveratrol, quercetin, hesperidin, curcumin, myricetin, and betulinic acid, which were proposed as SARS-CoV-2 inhibitors [159]. Regarding natural products, resveratrol, curcumin, and quercetin have demonstrated in vitro antiviral activity against SARS-CoV-2, and in vivo, a nebulised formulation has been demonstrated to alleviate the respiratory symptoms of COVID-19 [158,159,161].…”
Section: Drug Repurposing For Covid-19mentioning
confidence: 99%
“…A randomized clinical trial exhibited reduction in the symptoms of COVID-19 on using the phytochemical hesperidin. In another clinical study on antiviral activity of curcumin, it was found that the administration of nano-curcumin capsule orally could significantly reduce mRNA expression of pro-inflammatory cytokines (Das et al, 2023). The phytochemical silymarin, effective against SARS-CoV-2, is in Phase 3 of clinical trial (NCT04394208) and is in the recruitment stage.…”
Section: Phytochemical-loaded Nanoparticles In Covid-19mentioning
confidence: 99%